EM BUSCA DE UMA NUTRIÇÃO AMBIENTALMENTE ORIENTADA: DILEMAS E ALTERNATIVAS FRENTE AO SISTEMA ALIMENTAR CONTEMPORÂNEO DA GRANDE ACELERAÇÃO NO SUL DO BRASIL - Amaral, Marta Nichele do (2023)
Among the patterns of food production, choice and consumption in Brazilian society since the second half of the 20th century, the modernization of food systems has gone hand in hand with broader processes of industrialization, urbanization and internal migration and their processes have undergone important transformations. At the turn of the 20th century to the 21st, broader debates were incorporated, such as those that guided the search for food and nutritional security, but which also appear in the constitution of political and ethical movements that increasingly come closer to socio-environmental discussions linked to search for future food alternatives that are more sustainable and ethically oriented. The political process of food choice and consumption, for a portion of humanity that can orient itself, is part of new power relations linked to the eco-politicization of food, and decisions around what to produce, how to produce and how to consume food have environmental impacts, affecting the well-being of humans and non-humans. Thus, this thesis talks about practices, experiences, memories and decisions around how, for what, why and for whom to produce food and live off the land in the urban world and in a global context in which access to safe and healthy food is some of the biggest problems of the 21st century. I seek to analyse – based on an interdisciplinary discussion concerned with a more sustainable diet in comparison with a food regime marked by the Green Revolution in Brazil in the context of the Great Acceleration of the Anthropocene - practices and experiences lived and inscribed in the memory of organic producers from the interior of southern Brazil in order to understand them as food alternatives that make up what I call Environmentally Oriented Nutrition. I use oral life history, discussing the memory of the construction of eating practices in three municipalities in southern Brazil: Guarapuava/Paraná, Passo Fundo/Rio Grande do Sul and Chapecó/Santa Catarina. This discussion, which is part of the intersection of Environmental History, the history of sustainability, Nutrition and Community Development, concludes that urban or peri-urban gardens and a transition to agroecology are viable alternatives that are already well implemented and consolidated in regions such as those studied, and that they are marked by the diversity of agricultural practices, and that these alternative agricultures point to a healthy, safe and sovereign food future.